1988
DOI: 10.1063/1.340851
|View full text |Cite
|
Sign up to set email alerts
|

Iron nitride thin films prepared by facing targets sputtering

Abstract: Articles you may be interested inPolycrystalline iron nitride films fabricated by reactive facing-target sputtering: Structure, magnetic and electrical transport properties J. Appl. Phys. 110, 053911 (2011); 10.1063/1.3636364 Mn-Zn spinel ferrite thin films prepared by high rate reactive facing targets sputtering J. Appl. Phys. 93, 7996 (2003); 10.1063/1.1555842 Magnetic anisotropy and soft magnetism of iron nitride thin films prepared by facingtarget sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Believing that the Fe-N film was a polycrystalline mixture of Fe and a 00 -Fe 16 N 2 , they deduced that B s of a 00 -Fe 16 N 2 would be 2.83 T from the volume ratio of a 00 -Fe 16 N 2 in the film. Since the large saturated flux density is of importance, both theoretically and from the point of view of practical applications, many researchers have made great efforts using a variety of methods to synthesize a 00 -Fe 16 N 2 into bulk materials [2][3][4] and thin films [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Believing that the Fe-N film was a polycrystalline mixture of Fe and a 00 -Fe 16 N 2 , they deduced that B s of a 00 -Fe 16 N 2 would be 2.83 T from the volume ratio of a 00 -Fe 16 N 2 in the film. Since the large saturated flux density is of importance, both theoretically and from the point of view of practical applications, many researchers have made great efforts using a variety of methods to synthesize a 00 -Fe 16 N 2 into bulk materials [2][3][4] and thin films [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the α '' -Fe 16 N 2 phase is stable below 673 K and a slightly heated substrate will benefit the formation of α '' -Fe 16 N 2 [7,8] . Since the nitrogen is one of the key points to manipulate the phase compositions in the iron nitride films, the effect of nitrogen content are extensively studied 9,10 . However, there are few reports on the effect of bias voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore. the preparation of Fe 4N powder and the deposition of thin film have been widely studied [3][4][5]. The thin film is applicable to the magnetic recording head [6].…”
mentioning
confidence: 99%